Refractory Pseudomonas Bacteremia in a 2-Year-Old Sterilized by Bacteriophage Therapy. (22nd July 2017) - Duplessis, C; Biswas, B; Hanisch, B; Perkins, M; Henry, M; Quinones, J; Wolfe, D; Estrella, L; Hamilton, T
Abstract: Here, we report a complex case that involved a pediatric patient who experienced recalcitrant multidrug-resistant Pseudomonas aeruginosa infection complicated by bacteremia/sepsis; our antibacterial options were limited because of resistance, allergies, and suboptimal source control. A cocktail of 2 bacteriophages targeting the infectious organism introduced on 2 separate occasions sterilized the bacteremia.